Vaccination and the Prevention of Communicable Diseases in Healthcare Settings: Lessons from the Covid-19 Pandemic - Benjamin G Voyer; Claudine Provencher (SAGE Publishing, 2021)
With the number of Covid cases and Covid-related deaths continuing unabated, achieving a high vaccination coverage is essential to ensure the safety of staff and patients and resume normal hospital care admissions and operations. This article questions current strategies around vaccination in healthcare settings and proposes ways to understand and address vaccination hesitancy among staff. It offers insights on how to develop a multifaceted vaccination strategy, which takes into consideration vaccination hesitancy among healthcare professionals and community-specific factors. Drawing from social psychological theories, we suggest that the root of vaccination hesitancy lies in conflicting representations or cognitive polyphasia. In addition, we argue that current communication strategies mostly rely on rational arguments and ignores the importance of a more emotion-based approach.